AMIODARON SEBAGAI OBAT ANTI ARITMIA DAN PENGARUHNYA TERHADAP FUNGSI TIROID - Rampengan, Starry H. (Jurnal Biomedik : JBM, 2011)
Abstract: Amiodarone is a highly effective anti-arrhythmic agent used in certain arrhythmias from supraventricular tachycardia to life-threatening ventricular tachycardia. Its use is associated with numerous side-effects that could deteriorate a patient’s condition. Consequently, a clinician should consider the risks and benefits of amiodarone before initiating the treatment.The thyroid gland is one of the organs affected by amiodarone. Amiodarone and its metabolite desethyl amiodaron induce alterations in thyroid hormone metabolism in the thyroid gland, peripheral tissues, and probably also in the pituitary gland. These actions result in elevations of serum T4 and rT3 concentrations, transient increases in TSH concentrations, and decreases in T3 concentrations. Both hypothyroidism and hyperthyroidism are prone to occur in patients receiving amiodarone. Amiodarone-induced hypothyroidism (AIH) results from the inability of the thyroid to escape from the Wolff-Chaikoff effect and is readily managed by either discontinuation of amiodarone or thyroid hormone replacement. Amiodarone-induced thyrotoxicosis (AIT) may arise from either iodine-induced excessive thyroid hormone synthesis (type I, usually with underlying thyroid abnormality), or destructive thyroiditis with release of preformed hormones (type II, commonly with apparently normal thyroid glands). Therefore, monitoring of thyroid function should be performed in all amiodarone-treated patients to facilitate early diagnosis and treatment of amiodarone-induced thyroid dysfunction. Key words: Amiodarone, thyroid function, side effect, management, monitoring.     Abstrak: Amiodaron adalah obat antiaritmia yang cukup efektif dalam menangani beberapa keadaaan aritmia mulai dari supraventrikuler takikardia sampai takikardia ventrikuler yang mengancam kehidupan. Namun penggunaan obat ini ternyata menimbulkan efek samping pada organ lain yang dapat menimbulkan perburukan keadaan pasien. Sehingga, dalam penggunaan amiodaron, klinisi juga harus menimbang keuntungan dan kerugian yang ditimbulkan oleh obat ini. Salah satu organ yang dipengaruhi oleh amiodaron adalah kelenjar tiroid. Amiodaron dan metabolitnya desetil amiodaron memengaruhi hormon tiroid pada kelenjar tiroid, jaringan perifer, dan mungkin pada pituitari. Aksi amiodaron ini menyebabkan peningkatan T4, rT3 dan TSH, namun menurunkan kadar T3. Hipotiroidisme dan tirotoksikosis dapat terjadi pada pasien yang diberi amiodaron. Amiodarone-induced hypothyroidism (AIH) terjadi karena ketidakmampuan tiroid melepaskan diri dari efek Wolff Chaikof, dan dapat ditangani dengan pemberian  hormon substitusi T4 atau penghentian amiodaron. Amiodarone-induced thyrotoxicosis (AIT) terjadi karena sintesis hormon tiroid yang berlebihan yang diinduksi oleh iodium (tipe I, biasanya sudah mempunyai kelainan tiroid sebelumnya) atau karena tiroiditis destruktif yang disertai pelepasan hormon tiroid yang telah terbentuk (tipe II, biasanya dengan kelenjar yang normal). Pemantauan fungsi tiroid seharusnya dilakukan pada semua pasien yang diberi amiodaron untuk memfasilitasi diagnosis dan terapi yang dini terjadinya  disfungsi tiroid yang diinduksi amiodaron. Kata Kunci: Amiodaron, fungsi tiroid, efek samping, penanganan, pemantauan.